A Novel Multidrug Combination Mitigates Rat Liver Steatosis Through Activating AMPK Pathway During Normothermic Machine Perfusion. Issue 11 (November 2021) - Xu, Min; Zhou, Fangyu; Ahmed, Ola; Upadhya, Gundumi A.; Jia, Jianluo; Lee, Choonghee; Xing, Jianwei; Ye, Li; Shim, So Hee; Zhang, Zhengyan; Byrnes, Kathleen; Wong, Brian; et al.
Abstract : Background: Hepatic steatosis is now the leading cause of liver discards in deceased donors. Previous studies [Yarmush formula (Y) defatting] have successfully reduced the fat content by treating rat steatotic livers on extracorporeal normothermic machine perfusion (NMP) with a multidrug combination including the GW compounds that were linked to an increased risk of carcinogenesis. Methods: We developed a novel multidrug combination by replacing the GW compounds with 2 polyphenols, epigallocatechin-3-gallate (E) and resveratrol (R). Sixteen rat livers were placed on NMP and assigned to control, Y defatting, Y + E + R defatting, or Y′−GW + E + R defatting groups (Y′−GW = 90% dose-reduced Y defatting, n = 4/group). Results: All livers in defatting groups had significant decreases in hepatic triglyceride content at the end of the experiment. However, livers treated with our novel Y′−GW + E + R combination had evidence of increased metabolism and less hepatocyte damage and carcinogenic potential. Our Y′−GW + E + R combination had increased phosphorylation of AMP-activated protein kinase ( P  = 0.019) and acetyl-CoA carboxylase ( P  = 0.023) compared with control; these were not increased in Y + E + R group and actually decreased in the Y group. Furthermore, the Y′−GW + E + R group had less evidence of carcinogenic potential with no increase in AKT phosphorylation compared with control ( P  = 0.089); the Y ( P  = 0.031) and Y + E + R ( P  = 0.035) groups had striking increases in AKT phosphorylation. Finally, our Y′−GW + E + R showed less evidence of hepatocyte damage with significantly lower perfusate alanine aminotransferase ( P  = 0.007) and aspartate aminotransferase ( P  = 0.014) levels. Conclusions: We have developed a novel multidrug combination demonstrating promising defatting efficacy via activation of the AMP-activated protein kinase pathway with an optimized safety profile and reduced hepatotoxicity during ex vivo NMP. Abstract : Supplemental Digital Content is available in the text.